Tehokas, tehokkaampi, uupunut : työolotutkimuksen tuloksia 1977–1997 - Lehto, Anna-Maija; Sutela, Hanna (Tilastokeskus, 1998)
Työolotutkimus 1997
Keywords: tilastot; työolot; työelämä; työaika; työterveys; työviihtyvyys; työn kuormittavuus; työhyvinvointi; Työmarkkinat; Työolot